2004
DOI: 10.1292/jvms.66.1039
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation and Characterization of Murine Body Weight QTLs, <i>Bwq1</i> and <i>Bwq2</i>, Identified in C57BL/6J &times; KK-<i>A</i><sup>y</sup>/<i>a</i> F<sub>2</sub>-<i>A</i><sup>y</sup>/<i>a</i> Mice

Abstract: ABSTRACT. Body weight quantitative trait loci (QTLs), Bwq1 and Bwq2, identified previously in C57BL/6J × KK-A y /a F 2 -A y /a mice, were further confirmed and characterized. Body weight measurement was done from 21 days after birth (Day 21) through Day 100, at 10-day intervals. Bwq1 was statistically significant only on Days 40, 50, and 60, whereas Bwq2 was statistically significant on and after Day 40. When body weight gain (WG) between two successive weight measurements was evaluated, both Bwq1 and Bwq2 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Hrh1 is a plausible candidate gene for body weight QTL identified in the middle of chromosome 6 because Hrh1 constitutes part of the leptin signaling pathway in a way similar to MC4R, and because central administration of histamine decreases body weight and adiposity in A y mice [12]. I could not find any mutations in the coding sequence of Hrh1 in DDD and KK mice [23]. Kim et al [8] also analyzed Hrh1 as a candidate gene, and found no nucleotide changes between TallyHo and B6 alleles.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Hrh1 is a plausible candidate gene for body weight QTL identified in the middle of chromosome 6 because Hrh1 constitutes part of the leptin signaling pathway in a way similar to MC4R, and because central administration of histamine decreases body weight and adiposity in A y mice [12]. I could not find any mutations in the coding sequence of Hrh1 in DDD and KK mice [23]. Kim et al [8] also analyzed Hrh1 as a candidate gene, and found no nucleotide changes between TallyHo and B6 alleles.…”
Section: Discussionmentioning
confidence: 90%
“…For example, Bwq2 [24] and Tabw2 [8] apparently overlap with Bwdq2 and Obdq1 on chromosome 6. We previously identified Bwq2 as a modifier QTL for the A y allele in an F 2 intercross between B6 and obese KK-A y strains [23,24]. Similar to Bwq2, the effects of Bwdq2 and Obdq1 were stronger in F 2 A y than in F 2 non-A y mice.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These include macronutrient intake for carbohydrate (Minc2), which is responsible for preferring carbohydrate to fat in a cross of B6 and CAST/EiJ mice (48), body weight QTL (Bwq2), which is linked to body weight in a cross of B6 and KK-A y (56), and Obq14, which is linked to fat pad weight in a cross of NZO and SM mice (60). Bwq2 has been suggested as a genetic modifier of A y (57). Whether allelic variants at the tabw2 locus are responsible for the phenotypes linked to these QTLs could be determined through a haplotype analysis comparing the TH genotypes with those of the other susceptible and resistant strains (36) or by identification of the molecular bases of these loci.…”
Section: Discussionmentioning
confidence: 99%
“…A congenic mouse strain B6.TH-tabw2/tabw2, which carries obesity QTL tabw2 from the obese TallyHo mouse strain, had increased plasma leptin concentrations compared with control B6.TH-+/+ mice. Interestingly, tabw2 co-localized with Obdq1 [21] and Bwq2 [23,25] on chromosome 6.…”
Section: Females (N=298) C) Reference Map Position (Cm) Was Retrievementioning
confidence: 99%